Consensus recommendations for trabecular meshwork cell isolation, characterization and culture - Keller, Kate E.; Bhattacharya, Sanjoy K.; Borrás, Theresa; Brunner, Thomas M.; Chansangpetch, Sunee; Clark, Abbott F.; Dismuke, W. Michael; Du, Yiqin; Elliott, Michael H.; Ethier, C. Ross; Faralli, Jennifer A.; Freddo, Thomas F.; et al. (Experimental eye research, 2018)
Cultured trabecular meshwork (TM) cells are a valuable model system to study the cellular mechanisms involved in the regulation of conventional outflow resistance and thus intraocular pressure; and their dysfunction resulting in ocular hypertension. In this review, we describe the standard procedures used for the isolation of TM cells from several animal species including humans, and the methods used to validate their identity. Having a set of standard practices for TM cells will increase the scientific rigor when used as a model, and enable other researchers to replicate and build upon previous findings. •Comprehensive review of techniques to culture TM cells are presented.•Helpful tips for culturing TM cells are described.•First set of consensus standards for TM cell research is defined.